Prevalence, risk factors and lifestyle interventions of obstructive sleep apnea in adults: A scoping review - Ying, C.Y.; Hayatun Syamilah, M.N.; Nurul Anis, M.; Wan Nur Alis Arissya, W.S. (2021)
Introduction: Obstructive sleep apnea (OSA) is a sleep-disordered breathing which remains a critical concern in the obese population. It is associated with an increased risk of cardiovascular diseases. Objective: Our scoping review assesses the prevalence, risk factors, and lifestyle interventions of OSA among the adult population. Methodology: This scoping review uses the 5-stage methodological framework of Arksey and O'Malley. A comprehensive search of academic journals published from 2010 to 2020 was conducted in electronic databases such as PubMed, Med line in EBSCOhost, and Google Scholar. The initial search yielded 8,915 articles and a final result of 23 articles was selected. Results: The prevalence of OSA among obese adults ranged from 19.1% to 85.0%. The sig-nificant influence risk factors for OSA are older age, male, obesity, some components of metabolic syndrome such as hypertension, hyperglycemia, and dyslipidemia, physical inactivity, smoking, hours of work, and clinical symptoms, such as snoring, excessive day-time sleepiness, nocturnal awakenings, and respiratory pauses. Increasing daily physical activity, dietary modification, and weight loss are the lifestyle interventions for OSA. Conclusion: Obese individuals are at greater risk of developing OSA and are generally undiagnosed. It is important for healthcare professionals to screen individuals who are at high risk. Screening for OSA is recommended particularly among those obese older male adults with co-morbidities, presenting OSA clinical symptoms, and practicing unhealthy lifestyles. For individuals with mild to moderate OSA, lifestyle interventions are essential to decrease the prevalence of OSA, improve sleep quality, neurocognitive function, mood, and quality of life.